2012
DOI: 10.1186/1471-2261-12-69
|View full text |Cite
|
Sign up to set email alerts
|

Rate of cardiac arrhythmias and silent brain lesions in experienced marathon runners: rationale, design and baseline data of the Berlin Beat of Running study

Abstract: BackgroundRegular exercise is beneficial for cardiovascular health but a recent meta-analysis indicated a relationship between extensive endurance sport and a higher risk of atrial fibrillation, an independent risk factor for stroke. However, data on the frequency of cardiac arrhythmias or (clinically silent) brain lesions during and after marathon running are missing.Methods/ DesignIn the prospective observational “Berlin Beat of Running” study experienced endurance athletes underwent clinical examination (CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(57 citation statements)
references
References 35 publications
(41 reference statements)
1
54
1
1
Order By: Relevance
“…One notable ongoing study is the Berlin Beat of Running study, which is a prospective observational study which enrolled endurance athletes and followed up participants after 1 year for cardiac arrhythmia and brain lesions. [34] In conclusion, we found no significant increase in AF with a higher level of physical activity. This was the case considering the intensity, frequency of exercise as well as the case for athletes or sportsmen.…”
Section: Discussioncontrasting
confidence: 47%
“…One notable ongoing study is the Berlin Beat of Running study, which is a prospective observational study which enrolled endurance athletes and followed up participants after 1 year for cardiac arrhythmia and brain lesions. [34] In conclusion, we found no significant increase in AF with a higher level of physical activity. This was the case considering the intensity, frequency of exercise as well as the case for athletes or sportsmen.…”
Section: Discussioncontrasting
confidence: 47%
“…As previously reported [17], the original power calculation aimed for 110 participants in order to test the primary hypothesis (assuming that atrial fibrillation is found more frequently in endurance runners). For categorical data, absolute and relative frequencies were computed.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint of the study was defined as the frequency of cardiac arrhythmias in experienced marathon runners [16]. As one of the secondary endpoints, we observed the frequency of MRI-detected brain lesions before and immediately after a marathon race [17]. Here, we report the frequency of (clinically silent) acute ischemic, vasogenic or other brain lesions within two days after a marathon race.…”
Section: Objectivesmentioning
confidence: 96%
See 1 more Smart Citation
“…Los organizadores de carreras en el mundo como los maratones de Boston, Londres, Berlín, entre otros, realizan un tamizaje de riesgo o evaluaciones previas a los atletas, para detectar y reducir el riesgo cardiovascular 12,15,16 . Ante los eventos en las diferentes carreras, Maron reportó por primera vez que la incidencia de muerte súbita variaba entre 0,54 y 2,1 eventos por cada 100.000 participantes, con mayor afectación entre la sexta y octava década 7 .…”
Section: Introductionunclassified